2020
DOI: 10.1007/s10815-020-01844-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ABVD chemotherapy on ovarian reserve after fertility preservation in reproductive-aged women with Hodgkin lymphoma

Abstract: Research question How is ovarian reserve affected by chemotherapy in patients with Hodgkin lymphoma (HL) who undergo fertility preservation (FP)? Methods A retrospective study was conducted by reviewing medical records of 105 HL patients referred to the FP unit before starting adriamycin, bleomycin, vinblastine, and dacarbazine (ABVD) chemotherapy. Ovarian reserve was evaluated before chemotherapy and at the last follow-up using anti-Müllerian hormone (AMH) and antral follicle count (AFC) measurements. The dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…ABVD or BEACOPP regimens alone are very effective against blood cancer malignancies, yet, their further development is still needed. Evidence suggests that these regimens could negatively impact the fertility of both male and female patients [ 100 , 101 ]. In addition, Ramos et al reported that the ABVD regimen induces genomic chaos after one year of the treatment.…”
Section: Combination Of Vincristine With Procarbazine or Dacarbazinementioning
confidence: 99%
“…ABVD or BEACOPP regimens alone are very effective against blood cancer malignancies, yet, their further development is still needed. Evidence suggests that these regimens could negatively impact the fertility of both male and female patients [ 100 , 101 ]. In addition, Ramos et al reported that the ABVD regimen induces genomic chaos after one year of the treatment.…”
Section: Combination Of Vincristine With Procarbazine or Dacarbazinementioning
confidence: 99%
“…In both studies, none of the patients had received pelvic radiotherapy. Three additional papers (89 patients) reported a significant decrease in AMH before and after treatment for HL ( Krawczuk-Rybak et al , 2013a ; Berjeb et al , 2020 ; Policiano et al , 2020 ). A summary of results is presented in Table I and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Only the paper by Policiano et al (2020) reported AFC in HL survivors, and they mentioned a decrease in AFC post-treatment in comparison to values pre-treatment after a follow-up of ±2.8 years (44 patients, pre-treatment AFC 19 (interquartile range (IQR) 14–23), and post-treatment 10 (IQR 7–15), P value not given). Patients with an AFC below 6 or serum AMH below 0.84 ng/ml at baseline were excluded from this study.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, one of their most common effects is gonadal toxicity. Although therapies against HL are effective, they may contribute to fertility damage of patients inducing temporary or irreversible loss of fertility (Melo et al, 2019, Policiano et al, 2020. Due to chemotherapy and radiotherapy women affected by HL are exposed to an increased risk of early menopause and ovarian follicle depletion (Morgan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%